Necessity and proportionality in international peace and security law - (Lawyer) (New York, NY Oxford University Press, 2021)
Necessity and proportionality occupy a firm place in the international law governing the use of force by states. Perhaps most importantly for practical purposes, the exercise of the right of self-defense, as recognized in Article 51 of the United Nations Charter, is subject to the requirements of necessity and proportionality, as the International Court of Justice determined in the Nicaragua case. Necessity and proportionality are also firmly anchored in the international law governing armed conflicts. In its Nuclear Weapons Advisory Opinion, the International Court of Justice even referred to one articulation of the idea of necessity, that directed against the causing of unnecessary suffering, as one of two "cardinal principles" of this body of law. However, beyond statement in such general terms, the realms of uncertainty and controversy soon begin. It is far from clear, for example, how to distinguish with precision between necessity and proportionality in the international law on self-defense and, in immediate connection herewith, what it means precisely to say that forcible action taken in the exercise of self-defense must be proportionate. It is all the less clear what legal significance, if any, necessity and proportionality possess in other contexts of the international law governing the use of force"--
Necessity and proportionality in morality and law / Jeff McMahan -- On the continuous and concurrent application of ad Bellum and in Bello Proportionality / Eliav Lieblich -- The essential link between proportionality and necessity in the exercise of self-defense / Geoffrey S. Corn -- The unwilling and unable test for extraterritorial defensive force : why force is permitted against the territorial state / Jens David Ohlin -- Drones programs, the individualization of war, and the ad Bellum Principle of Proportionality / Rebecca Mignot-Mahdavi --The quest for an internal Jus ad Bellum : international law's missing link, mere distraction, or Pandora's Box? / Tom Ruys -- Article 51's reporting requirement as a space for legal argument and factfulness / Larissa van den Herik -- Sequences in military necessity for the Jus in Bello / Dino Kritsiotis -- Practical and conceptual challenges to doctrinal military necessity / Robert Lawless -- Considerations of necessity under Article 57(2)(a)(ii), (c), and (3) and proportionality under Article 51(5)(b) and Article 57(2)(b) of additional Protocol I : is there room for an integrated approach? / Wolff Heintschel von Heinegg -- Specifying the proportionality test and the standard of due precaution : problems of prognostic assessment in determining the meaning of "may be expected" and "anticipated" / Stefan Oeter -- The proportionality rule and mental health harm in war / Sarah Knuckey, Alex Moorehead, Audrey McCalley, and Adam Brown -- Towards the special computer law of targeting : "fully autonomous" weapons systems and the proportionality test / Masahiro Kurosaki -- The duty to pay reparations for the violation of the prohibition of the use of force in international relations and the Jus Post Bellum / Elisabeth Günnewig.
Includes bibliographical references and index.
Keywords: Intervention (International law) -- Electronic books; Necessity (International law); Proportionality in law